Professional Performance of Nutrition Graduates from a Tertiary Education Institution in Paraná - Brazil - Panice, Gislaine Mara Neiro (2008)
The study it objectified to evaluate the professional performance of the nutritionists egresses of the CESUMAR - University Center of Maringá that forms professionals with generalists profiles, formed in the period of 2004 the 2006. The data had been collected through a structuralized questionnaire. The analysis was quali-quantitative transversal line, where if it identified to the area and city of performance and the percentage of after-graduation. They had participated 48,4 % of the egresses formed in the period, after analysis verified that 47,93% act in Clinical Nutrition, 31,4% in Units of Feeding and Nutrition, 9,09% in Sportive Nutrition, 26% in Public Health, 6,61% in Teaching Activities, 5,79% in marketing, 2,48% in Industrial of Foods and 11,57% in other areas, the city of bigger performance were Maringá (51,2%). The courses of graduation in nutrition need to know the performance of its egresses and its level of satisfaction, why this becomes a tool important to guide action in favor of improvements of the courses.